Performing Hypermasculinity in Billboard Ads and Malls - Devilles, Gary C (Archīum Ateneo, 2013)
Images of masculinities are used in ad placements in TV, movies, and billboards. Aside from the consumerist nature of such images, I wonder if these constitute city dynamics, such that life in the city can be construed as fantastical or spectacular, and whether such fantasy is masculine in orientation. This work investigates masculinity not just as a product of city living, but also as a phenomenon in which the city seemingly assumes a muscular stance, manifesting in its ensuing power relations. I focus on underwear billboards and malls in Manila as texts by which hypermasculinity, this male fantasy, is produced, performed, becomes visible. I also discuss Susan Bordo’s assertion that the study of masculinity is in no way isolated from feminism. Through her account of her father’s life, and analyses of advertisements and TV shows, she argues that male experiences of shame, exhaustion with cultural expectations, or the failure of the male body to live up to those expectations, resonate with the feminists’ struggle for emancipation. In this light I approach masculinity and city studies as mutually inclusive fields, underlying a male fantasy, a hypermasculinity, which is all too visible, dominating and shaping our lives. Hypermasculinity feeds on the culture of consumption, the fetishism of masculine virility and objectification of women, on the panoply of images evoking beauty and nostalgia. I argue that the city—specifically Manila—being hypermasculine, hides its ugliness and shame, and its development is posturing, aggressive behaviour, compensating for irreconcilable contradictions and alienated relationships.